Gradual Changes of Gut Microbiota in Weaned Miniature Piglets - Hu, Jun; Nie, Yangfan; Chen, Jianwei; Zhang, Yong; Wang, Zhichang; Fan, Qiwen; Yan, Xianghua (Frontiers in Microbiology, 2016)
Colonization of gut microbiota in mammals during the early life is vital to host health. The miniature piglet has recently been considered as an optimal infant model. However, less is known about the development of gut microbiota in miniature piglets. Here, this study was conducted to explore how the gut microbiota develops in weaned Congjiang miniature piglets. In contrast to the relatively stabilized gut fungal community, gut bacterial community showed a marked drop in alpha diversity, accompanied by significant alterations in taxonomic compositions. The relative abundances of 24 bacterial genera significantly declined, whereas the relative abundances of 7 bacterial genera (Fibrobacter, Collinsella, Roseburia, Prevotella, Dorea, Howardella, and Blautia) significantly increased with the age of weaned piglets. Fungal taxonomic analysis showed that the relative abundances of 2 genera (Kazachstania and Aureobasidium) significantly decreased, whereas the relative abundances of 4 genera (Aspergillus, Cladosporium, Simplicillium, and Candida) significantly increased as the piglets aged. Kazachstania telluris was the signature species predominated in gut fungal communities of weaned miniature piglets. The functional maturation of the gut bacterial community was characterized by the significantly increased digestive system, glycan biosynthesis and metabolism, and vitamin B biosynthesis as the piglets aged. These findings suggest that marked gut microbial changes in Congjiang miniature piglets may contribute to understand the potential gut microbiota development of weaned infants.